The Power of Collaboration: Resilience of the Apparel Industry in Ghana during the COVID-19 Pandemic - Cynthia Akua Chichi; Benjamin Kwablah Asinyo; Eunice Owusu-Antwi; Ebenezer Owusu-Addo; Benjamin Tawiah; Ebenezer Kofi Howard (Fashion and Textiles Review, 2025)
Purpose: The purpose of this study was to explore the collaborative efforts that were utilised in the face of the global COVID-19 pandemic, where industries worldwide faced unparalleled challenges that disrupted standards and demanded rapid adjustment. This study examines how public-private collaboration enhanced operational resilience in Ghana's apparel industry during COVID-19 supply chain disruptions, using Personal Protective Equipment (PPE) production as a critical adaptive response.